Assessment of risk factor for oral submucous fibrosis in patients- a retrospective study - GANAPATHI, AMANTHI; VIJAYAKUMAR, JAGADISH; JEEVITHA, M. (The journal of contemporary issues in business and government, 2021)
Oral submucous fibrosis(OSMF) is a precancerous condition progessive disorder which is caused because of the tobacco products usage,consumption of spicy foods.It will cause rigidity of the tongue,lip and palate in the severe cases it will cause limited mouth opening.Parts which gets affected will be oral cavity,pharynx and upper third of esophagus.This study is done to assess risk factor oral submucous fibrosis (OSMF) in patients getting treated in saveetha dental college and hospitals.A retrospective study was conducted in dental hospitals in departments of oral and maxillofacial surgery,department of oral medicine.Patient data was collected from hospital records.In our study we found that use of tobacco smoking (31.2%),pan chewing(34.4%),Tobacco chewing(23.7%), and betel nut chewing(9.7%).Total sample size(n=93) 7 female patients ,86 male patients.Most affected age group will be (41-50 years old)-26.9%.Our study pan chewing and tobacco products among the 41-50 years old male population were significantly high in association with the risk factor of OSMF.